AB0308 Optimal timing for tocilizumab administration to patients with rheumatoid arthritis in japan based on a cost-effectiveness analysis using the iorra cohort study. (23rd January 2014) - Tanaka, E.; Inoue, E.; Hoshi, D.; Shidara, K.; Sato, E.; Inoue, Y.; Seto, Y.; Nakajima, A.; Momohara, S.; Taniguchi, A.; Yamanaka, H.
Abstract : Background: Rheumatoid arthritis (RA) imposes a considerable economic burden on societies. Early, adequate control of disease activity can prevent permanent disability and decrease the overall costs of treatment. In clinical studies, an anti–interleukin-6 receptor antibody (tocilizumab; TCZ) was shown to remarkably improve disease conditions in RA patients. Objectives: We investigated the optimal timing for TCZ administration to RA patients from the perspective of cost-effectiveness using an RA cohort (Institute of Rheumatology, Rheumatoid Arthritis; IORRA) database. Methods: Markov model-based probabilistic simulations from the societal perspective were performed using six hypothetical populations of 10, 000 patients that differed in physical dysfunction severity based on the Japanese version of the Health Assessment Questionnaire (J-HAQ) scores (<0.6, 0.6-1.1, 1.1-1.6, 1.6-2.1, 2.1-2.6, and 3 2.6) at the start of treatment (initial J-HAQ scores). The cycle length was six months. Patients who had failed > 1 DMARD and for whom TCZ had been used in Japan between April 2007 and April 2011 (TCZ group) and patients similar in background to the TCZ group who started MTX (MTX group) were extracted from the IORRA database using a pair-matching method. Health states in the model were defined based on the six J-HAQ levels, which corresponded to cost and utility. All model parameters, such as transition probabilities for health states, utility, and medical costs, were determined for each health state based on clinical data in real-world settings from IORRA. Quality-adjusted life years (QALYs) and lifetime cumulative costs in the TCZ and MTX groups and an incremental cost-effectiveness ratio (ICER) were estimated for the six hypothetical populations. A lifetime horizon and a discount rate of 3% per year for both health benefits and costs were assumed. Results: Clinical data for two groups of 104 patients each (mean age and baseline J-HAQ scores were 57.0 years and 1.27, respectively, in the TCZ group, and 57.6 years and 1.26, respectively, in the MTX group) were used to calculate model parameters. QALYs decreased considerably with increased initial J-HAQ scores, whereas almost no apparent differences in lifetime cumulative costs were observed in either group (Table ). QALYs were always higher in the TCZ group, regardless of initial J-HAQ scores. ICER was best (21, 604 EUR) for patients with initial J-HAQ scores of 0.6-1.1 and increased to > 100, 000 EUR for patients with initial J-HAQ scores of > 2.1 (1 EUR = 120 JPY in 2012). Image/graph: Conclusions: TCZ might be most cost-effectively used for RA patients whose initial J-HAQ's are 0.6-1.1. This suggests that early administration of TCZ is useful prior to the development of irreversible physical disability in RA patients. Disclosure of Interest: E. Tanaka: None Declared, E. Inoue: None Declared, D. Hoshi: None Declared, K. Shidara: None Declared, E. Sato: None Declared, Y. Inoue: None Declared, Y. Seto: None Declared, A. Nakajima: None Declared, S. Momohara: None Declared, A. Taniguchi: None Declared, H. Yamanaka Grant/research support from: IORRA study is supported by Asahikasei Kuraray Medical Co., Ltd., Abbott Japan Co., Ltd., Asahikasei Pharma Corporation, Astellas Pharma Inc., AstraZeneca K.K., Bristol-Myers Squibb, Chugai Pharmaceutical Co., Ltd., Daiichi Fine Chemical Co., Ltd., Daiichi Sankyo Co., Ltd., Dainippon Sumitomo Pharma Co., Ltd., Eisai Co., Ltd., GlaxoSmithKline K.K., Hisamitsu Pharmaceutical Co., Inc., Janssen Pharmaceutical K.K., Japan Tobacco Inc., Kaken Pharmaceutical Co., Ltd., Kissei Pharmaceutical Co., Ltd., Kowa Pharmaceutical Co. Ltd., Maruho Co., Ltd., Mitsubishi Chemical Medience Corporation, Mitsubishi Tanabe Pharma Corporation, Mochida Pharmaceutical Co. Ltd., MSD K.K., Mundipharma K.K., Nippon Chemiphar Co., Ltd., Nippon Shinyaku Co., Ltd., Novartis Pharma K.K., Otsuka Pharmaceutical Co., Ltd., Pfizer Japan Inc., Sanofi-Aventis K.K., Santen Pharmaceutical Co., Ltd., Sanwa Kagaku Kenkyusho Co., Ltd., Sekisui Medical Co., Ltd., Shionogi Co., Ltd., Taishotoyama Pharmaceutical Co., Ltd., Takeda Pharmaceutical Co. LTD., Teijin Pharma Limited, Torii Pharmaceutical Co., Ltd., UCB Japan Co. Ltd., ZERIA Pharmaceutical Co., Ltd., Consultant for: Abbott Japan Co., Ltd, AstraZeneca K.K., Bristol-Myers Squibb, Chugai Pharmaceutical Co., Ltd., Eisai Co., Ltd., Janssen Pharmaceutical K.K., Mitsubishi Tanabe Pharma Corporation, Pfizer Japan Inc., Takeda Pharmaceutical Co. LTD., Teijin Pharma Limited, UCB Japan Co. Ltd.